A Genetic Variant of miR-34a Contributes to Susceptibility of Ischemic Stroke Among Chinese Population - Wei, Gui-Jiang; Yuan, Ming-Qing; Jiang, Li-He; Lu, Yu-Lan; Liu, Chun-Hong; Luo, Hong-Cheng; Huang, Hua-Tuo; Qi, Zong-Quan; Wei, Ye-Sheng (Frontiers in Physiology, 2019)
miRNAs are small non-coding RNAs modulating gene expression, and variants in miRNA genes are involved in the pathogenesis of ischemic stroke (IS). However, the effect of miR-34a polymorphisms on IS susceptibility has rarely been reported. In the present study, we investigated the association between rs12128240, rs2666433, and rs6577555 of the miR-34a gene and IS susceptibility. Snapshot assay was used to detect miR-34a polymorphisms in 548 IS patients and 560 controls. Relative expression of miR-34a was measured by quantitative real-time PCR. We found that rs2666433 was associated with a significantly increased risk of IS (AA vs. GG: OR = 1.61, 95% CI = 1.05–2.52, P = 0.031; AA vs. GG+GA: OR = 1.58, 95% CI = 1.05–2.45, P = 0.026). For the IS subtypes, rs2666433 was associated with large artery atherosclerosis (AA vs. GG: OR = 2.09, 95% CI = 1.16–3.51, P = 0.007; AA vs. GG+GA: OR = 2.02, 95% CI = 1.15–3.33, P = 0.007; A vs. G: OR = 1.36, 95% CI = 1.07–1.81, P = 0.021). Additionally, the level of miR-34a was significantly up-regulated in IS patients compared to the controls (P < 0.001), and patients with rs2666433 AA genotype had a higher level of miR-34a than those with GG+GA genotypes (P < 0.001). Furthermore, increased level of homocysteine was observed in IS patients compared to the controls (P < 0.001), especially in patients carrying the rs2666433AA genotype compared to those carrying the rs2666433 GG+GA genotypes (P < 0.001). However, no significant association between rs12128240 or rs6577555 and IS was found. Collectively, our study found the association between miR-34a polymorphisms and the risk of IS among the Chinese population. The results may provide an explanation for etiology of IS and a potential biomarker or therapeutic target for IS. HIGHLIGHTS - MiR-34a rs2666433 polymorphism was associated with an increased risk of ischemic stroke. - The level of miR-34a was significantly up-regulated in ischemic stroke patients compared with controls, and patients with rs2666433 AA genotype had a higher level miR-34a than those with GG+GA genotypes. - Furthermore, increased level of homocysteine was showed in IS patients compared to controls, and in patients carrying the rs2666433AA compared to those carrying the rs2666433 GG+GA.